Effects of Using Flashcards to Teach Vocabulary in Public Schools in Sidoarjo, East Java: Pengaruh Penggunaan Flashcards Untuk Mengajar Kosakata di Sekolah Umum di Sidoarjo, Jawa Timur - Febriyanti, Virda; Novita, Dian (Indonesian Journal of Education Methods Development, 2023)
The purpose of this study is to know the effect of using flashcards for teaching vocabulary of the third graders at a public elementary school in Sidoarjo, East Java, Indonesia. This study used quantitative research with a pre-experimental design by applying pre-test and post-test instruments. Quantitative data were analyzed using the Independent T-test formula test to determine the difference between pre-test and post-test on the students’ achievement using flashcards. In the pre-test value there is an average value of 50 and the post-test value has an average value of 66 while for the t-test value of 7.615 was higher than t-table 2.003 at the level of significant 0.05 with the degree of freedom (df ) 56. The results of this study found that the use of flashcards had an effect on the students’ achievement of the vocabulary mastery.